Acute obstetric and gynecologic emergencies among pregnant women in a tertiary care hospital, Iran - Shahnaz Barat; Zinatosadat Bouzari; Novin Nikbakhsh; Mojgan Naeimi Rad (Caspian Journal of Reproductive Medicine, 2015)
Background: Acute abdominal pain is a medium or severe abdominal pain that can lead to a life threatening for pregnant women and frequently requires urgent investigation and management. The aim of this study was to assess the causes and the presentation of acute abdomen among pregnant women admitted at the gynecology and an obstetrics ward of the hospital.